Self-Organized Morphology in Nanostructured Materials - Al-Shamery, Katharina H. (Springer, 2017)
Integrating nano and microphysical effects, this book's team of expert authors offers new insights into self-organized structure formation in nanomaterials. A major question addressed in this book is the role of spatial and temporal order. In particular, you'll discover how to apply concepts developed on macroscopic and microscopic scales to structure formation occurring on nanoscales, a key focus of interest at the frontiers of science.